(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was carried out in the peri urban areas of Surat city of Gujarat to find out the adoption of improved buffalo husbandry practices. A random sample of 50 buffalo farm owners were selected and interviewed for the interview schedule prepared about adoption of improved dairy husbandry practices in six major aspects of housing, feeding, breeding, health care, milking and calf rearing management was studied. Housing in separate located place (100%), providing proper floor space (98%) and proper height and ventilation (90%) were more adopted in housing practices. Provision of clean and fresh drinking water (100%), feeding extra ration to advance pregnant animals (64%) and feeding balance concentrate mixture on the basis of milk production (64%) were more adopted in feeding management. In adoption of breeding management, keeping watch on oestrus cycle and heat symptoms of animals (100%), artificial insemination of animals (100%) and practicing pregnancy diagnosis between 60-90 days after service (91%) were more adopted by buffalo owners. Observing animals daily for signs of sickness (100%), timely and regularly vaccination (100%) and treatment of reproductive disorders (75%) were more adopted by respondents in health care management practices. In milking and calf rearing practices, washing pails and hands before milking (100%) and regularity in milking time (100%), early solid feeding (100%) and milk feeding to calves up to three months of age (96%) were more adopted by the buffalo owners.